2022
DOI: 10.1192/j.eurpsy.2022.2011
|View full text |Cite
|
Sign up to set email alerts
|

Late onset schizophrenia and delusional disorder: activity of platelet energy, glutamate, and glutathione metabolizing enzymes

Abstract: Introduction Alterations of glutamate, energy and glutathione metabolism contribute to the pathogenesis of psychotic disorders Objectives Revealing clinical-biological correlations in patients with late onset schizophrenia and delusional disorder by determining clinical parameters and activity of platelet enzymes of energy, glutamate, and glutathione metabolism. Methods 27 women of 45-80 years old were studied, with late onset schizophrenia or delusional disorder. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, when examining the implications for altered glutamate and GABA metabolism in the dorsolateral prefrontal cortexes of older patients with schizophrenia, no significant differences were observed in the levels of GDH activity in these areas between the test and control groups [216]. In late-onset schizophrenia and delusional disorders, changes in glutamate and glutathione metabolism, including changes in metabolic enzymes such as GDH, affect the course of the illness [217]. It was also shown that serum GDH activity tended to be lower in people with schizophrenia with late dyskinesia than in people with schizophrenia without it [218].…”
Section: Gdh In Psychiatrymentioning
confidence: 99%
“…However, when examining the implications for altered glutamate and GABA metabolism in the dorsolateral prefrontal cortexes of older patients with schizophrenia, no significant differences were observed in the levels of GDH activity in these areas between the test and control groups [216]. In late-onset schizophrenia and delusional disorders, changes in glutamate and glutathione metabolism, including changes in metabolic enzymes such as GDH, affect the course of the illness [217]. It was also shown that serum GDH activity tended to be lower in people with schizophrenia with late dyskinesia than in people with schizophrenia without it [218].…”
Section: Gdh In Psychiatrymentioning
confidence: 99%